2061. Impact of a Penicillin-Binding Protein 2a Rapid Diagnostic Test on Patients Who Present with Staphylococcus aureus Orthopedic Hardware Infections. (26th November 2018) - Hayes, Jillian; Nesbitt, Whitney; Wright, Patty; Greene, Matthew; Nelson, George
Abstract: Background: Waiting for culture availability from orthopedic hardware (HW) infections delays patient discharge and time to definitive antimicrobial therapy. In February 2017, Vanderbilt University Hospital (VUH) implemented a penicillin-binding protein 2a-based rapid diagnostic, Alere ®, to differentiate methicillin-susceptible S. aureus (MSSA) and methicillin-resistant S. aureus (MRSA) from tissue sample growth. In other settings, use of Alere ® demonstrated decreased time to definitive therapy with and without stewardship intervention. However, no studies to date have examined the impact of Alere ® in the orthopedic HW infection population. Methods: We performed a retrospective study of patients ≥18 years of age admitted to VUH with a culture-positive, monomicrobial, S. aureus orthopedic HW infection. Select ICD-10 codes related to orthopedic HW infections were used to identify potential patients. Exclusion criteria included concomitant bacteremia or polymicrobial infections. Patients with sterile site cultures obtained from August 2016 to January 2017 were included in the pre-Alere ® group and February 2017 to September 2017 in the post-Alere ® group. The primary outcome was time to appropriate antibiotic, defined as cefazolin or nafcillin for MSSA, and vancomycin for MRSA. Daptomycin and linezolid were acceptable alternatives in the case of prior vancomycin failure, or severe, documented reaction to vancomycin. Results: ICD-10 codes identified a total of 331 patients, with 29 (8.7%) demonstrating monomicrobial S. aureus HW infections (52% MSSA). There were 11 (38%) and 18 (62%) patients in pre- and post-Alere ® groups, respectively. Alere ® results provided definitive methicillin susceptibility 31.9 (range 19.5–46.1) hours before standard culture results. Time to appropriate antibiotic was 41.8 hours less in post-Alere ® group ( P = 0.009). Duration of empiric Gram-negative coverage was significantly reduced in the post-Alere ® group ( P = 0.029). Overall length of stay was unchanged between the groups ( P = 0.873). Conclusion: Introduction of Alere ® reduced time to appropriate therapy and reduced empiric Gram negative coverage in patients being treated for orthopedic hardware infections. Disclosures: All authors: No reported disclosures.